Attractiveness of copperleaf-based bait to leaf-cutting ants - Nagamoto,Nilson Satoru (2011)
Leaves of copperleaf (Acalypha spp.) are greatly accepted by leaf-cutting ants and therefore used to maintain colonies in the laboratory. In order to determine the attractive potential of granulated bait of Acalypha wilkesiana leaves versus citrus pulp, currently used in commercial baits, an evaluation was performed, by using the leaf-cutting ant Atta sexdens rubropilosa as model. The handmade non-toxic baits contained powder (90% w/w) of either citrus pulp or A. wilkesiana were offered simultaneously in the foraging arena until the total loading of one of them. Results showed that copperleaf baits are less attractive than the citrus ones, which invalidates the viability of the substitution.